Are adherence to the Mediterranean diet and siesta individually or jointly associated with blood pressure in Spanish adolescents? Results from the EHDLA study - Mesas, Arthur Eumann; Jimenez-López, Estela; Martínez-Vizcaíno, Vicente; Fernández-Rodríguez, Rubén; Bizzozero-Peroni, Bruno; Garrido-Miguel, Miriam; Cavero-Redondo, Iván; López-Gil, José Francisco (Frontiers in Public Health, 2022)
Background: Both dietary and sleep patterns can influence both blood pressure (BP) levels, but these associations have been understudied in adolescents. Furthermore, it is not known whether diet and sleep could exert a synergistic effect with respect to the maintenance of optimal BP levels in this population. Objective: To investigate the relationship of BP levels with the combination of higher adherence to the Mediterranean diet (MD) and the habit of siesta (daytime napping) in Spanish adolescents. Methods: A cross-sectional study was conducted with data from a representative population-based sample of adolescents (12-17 years of age) from the Valle de Ricote (Region of Murcia, Spain). Adherence to the MD was assessed with the Mediterranean Diet Quality Index in Children and Adolescents (KIDMED), and the frequency and duration of siesta were self-reported. Objective measurements of systolic and diastolic BP were obtained under standardized conditions. Statistical procedures included logistic and generalized regression models adjusted for sex, age, socioeconomic status, body mass index, total energy intake, nighttime sleep duration, and moderate-to-vigorous physical activity. Results: Of the 695 adolescents studied (mean age 13.9 ± 1.5 years; 56.1% female), 37.1% (n=258) had high adherence to the MD, and 20.6% (n=143) reported frequent siesta. In the completely adjusted models, compared to adolescents with low MD adherence and no or infrequent siesta, those with high MD adherence and frequent siesta were less likely to have high-normal BP or hypertension (odds ratio, OR: 0.48; 95% confidence interval: 0.26, 0.88) and showed slightly lower systolic BP (ß-coef.: -2.93; 95% CI: -5.45, -0.40). Conclusions: Greater adherence to the MD and frequent siesta have a synergistic effect on maintaining lower BP levels in adolescence. These findings reinforce that adherence to both Mediterranean lifestyle behaviors early in life may be an important strategy to prevent hypertension throughout adulthood.